Fuzzy solution of nonlinear Boussinesq equation. Issue 6 (1st November 2022) - Tzimopoulos, Christos; Papadopoulos, Kyriakos; Papadopoulos, Basil; Samarinas, Nikiforos; Evangelides, Christos
Abstract: In this paper, the solution of the one-dimensional second-order unsteady nonlinear fuzzy partial differential Boussinesq equation is examined. The physical problem concerns unsteady flow in a semi-infinite unconfined aquifer bordering a lake. In the examined problem, there is a sudden rise and subsequent stabilization of the lake's water level, thus the aquifer is recharging from the lake. The aquifer boundary conditions are considered fuzzy and, therefore, ambiguities are created to the solution of the overall physical problem. Then, the fuzzy problem is translated to a system of crisp boundary value problems. By using a Boltzmann transformation, the crisp problem is transformed into an integro-differential equation and solved with the help of a special numerical method. This method has a simple iterative procedure, which converges rapidly and is proven very accurate in comparison with other analytical methods. Additionally, the algebraic equation estimates very close to the storage coefficient, the flux at the stream-aquifer origin, and the water stored volume with respect to other exact solutions. This method is very useful for practical cases (artificial recharge problems, irrigation, and drainage projects), giving the possibility to decision-makers to take the right decision. HIGHLIGHTS: Solution of the fuzzy unsteady nonlinear flow. Application of recharging an aquifer. Numerical solution of the fuzzy integro-differential equation. Accurate estimation of recharge coefficient. Accurate estimation of stored volume/width and flux boundary at x = 0. Application of a special numerical algorithm.